Multiple-channel double-layer flat membrane component device - QIU TAO; LIU XUHONG; GAO LINDONG (2015)
The utility model relates to a multiple-channel double-layer flat membrane component device which comprises a first membrane box and a second membrane box, wherein the first membrane box is arranged on the upper side of the second membrane box; an aeration box is arranged on the lower side of the second membrane box; the aeration box comprises an aeration pipeline; at least two double-water outlet membrane elements are arranged in each of the first membrane box and the second membrane box; two water outlets are formed in any one of the two double-water outlet membrane elements; each of the water outlets is connected with a water collecting pipe; one end of each of the water collecting pipes extends to the outer sides of the first membrane box and the second membrane box. According to the multi-channel double-layer flat membrane component device, the loading intensity of the flat membrane component device is increased, the occupied area is reduced, the utility rate of the aeration is greatly improved, the water collecting process is shortened by the double-water outlet elements, the suction energy consumption of filtered water is reduced, on-line cleaning of membranes can be facilitated, and the on-line cleaning efficiency is improved.